Comparison of selected trenchless technologies in renovation and reconstruction of transit water supply network DN600 - Gorczowski, Wojciech; Piechurski, Florian (Instal, 2021)
The aim of this work is the technology comparison for the modernization of the DN600 steel water supply. In the analysis, four variants were adopted to modernize the water supply system: I – Swagelining, II – Long relining, III – Cementing and IV – Flexible sleeve. The choice of technology was made taking into account the parameters characterizing each of the methods: execution costs, completion date, interference with the environment. The most optimal of all compared technologies, securing the water supply through cementing technology was selected. The technology is based on covering the inner surface of the existing steel water supply with cement mortar. The selected technology seems to be the best among those compared in the modernization of the analyzed water supply system due to the technical condition of the water supply and its endurance capabilities in the period of planned operation. This method allows to achieve all assumed modernization goals. It ensures tightness, improvement of hydraulics, protects the water supply against corrosion. It is the cheapest and the least complicated method. It also has the shortest implementation time.
Keywords: water supply network; trenchless repair methods; modernization cost analysis; duration of works